GALNT3 Maintains the Epithelial State in Trophoblast Stem Cells - Deepthi Raghu; Robert J. Mobley; Noha A.M. Shendy; Charles H. Perry; Amy N. Abell (Cell Reports, 2019)
Summary: O-GalNAc glycosylation is initiated in the Golgi by glycosyltransferases called GALNTs. Proteomic screens identified >600 O-GalNAc-modified proteins, but the biological relevance of these modifications has been difficult to determine. We have discovered a conserved function for GALNT3 in trophoblast stem (TS) cells, blastocyst trophectoderm, and human mammary epithelial cells (HMECs). The loss of GALNT3 expression in these systems reduces O-GalNAc glycosylation and induces epithelial-mesenchymal transition. Furthermore, Galnt3 expression is reduced in aggressive, mesenchymal claudin-low breast cancer cells. We show that GALNT3 expression controls the O-GalNAc glycosylation of multiple proteins, including E-cadherin in both TS cells and HMECs. The loss of GALNT3 results in the intracellular retention of E-cadherin in the Golgi. Significantly, re-expression of GALNT3 in TS cells increases O-GalNAc glycosylation and restores the epithelial state. Together, these data demonstrate the critical biological role of GALNT3 O-GalNAc glycosylation to promote the epithelial phenotype in TS cells, blastocyst trophectoderm, and HMECs. : Raghu et al. demonstrate that O-GalNAc glycosylation is critical for epithelial state maintenance in trophoblast stem cells and HMECs. MAP3K4 promotes GALNT3 O-GalNAc modification of E-cadherin. Loss of GALNT3 results in the retention of E-cadherin in the Golgi. GALNT3 re-expression restores cell surface localization of E-cadherin, protecting the epithelial state. Keywords: epithelial-to-mesenchymal transition, EMT, MAP3K4, trophoblast stem cells, blastocyst, GALNT3, O-GalNAc glycosylation, E-cadherin, histone deacetylase, HDAC6